2021
DOI: 10.1111/1752-1688.12963
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrological Urban Heat Island: Determinants of Acute and Chronic Heat Stress in Urban Streams

Abstract: During and after rainfall events, the interaction of precipitation with hot urban pavements leads to hot runoff, and its merger with urban streams can result in an abrupt change in water temperature that can harm aquatic ecosystems. To understand this phenomenon and its relation to land cover and hydrometeorological parameters, we analyzed data spanning two years from 100 sites in the eastern United States. To identify surges, we first isolated temperature jumps of at least 0.5°C over 15 min occurring simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…Events with temperature increases were more likely to occur in the afternoon/evening, whereas stream temperature decreases typically occurred earlier in the year (before the middle of July, day of year 200). The finding that time of day is linked to the occurrence of temperature increases is in agreement with work by Zahn et al (2021), who quantified heat pulses across 100 watersheds in the midwestern and eastern US, and Hester and Bauman (2013), who observed water temperatures near urban storm sewer outfalls in Virginia, USA. Both studies observed a greater frequency and magnitude of temperature increases in the afternoon when pre‐event discharge and pre‐event temperatures were higher.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Events with temperature increases were more likely to occur in the afternoon/evening, whereas stream temperature decreases typically occurred earlier in the year (before the middle of July, day of year 200). The finding that time of day is linked to the occurrence of temperature increases is in agreement with work by Zahn et al (2021), who quantified heat pulses across 100 watersheds in the midwestern and eastern US, and Hester and Bauman (2013), who observed water temperatures near urban storm sewer outfalls in Virginia, USA. Both studies observed a greater frequency and magnitude of temperature increases in the afternoon when pre‐event discharge and pre‐event temperatures were higher.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the shape and form of these stream temperature responses may vary, and (gradual) temperature increases do not appear to be the only possible stream temperature response during a storm event. Zahn et al (2021) observed that temperature increases may be followed by a subsequent rapid decrease in water temperature, a pattern we will refer to as a ‘heat pulse’ in our study. However, further exploration of this phenomena has been limited.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…on DO dynamics in streams and estuaries (Apple et al, 2006;Caffrey, 2003;Caffrey et al, 2014). Highlighted results link climate change and urbanization to thermal pollution of urban streams following rain events (Zahn et al, 2021), and show connections of elevated global temperatures with decreased primary production (Song et al, 2018) and increased planktonic N demand (Toseland et al, 2013). Therefore, the combined effects of watershed urbanization and global temperature increase on phytoplankton could exacerbate DO dynamics in estuaries and significantly shift the range of DO baseline.…”
mentioning
confidence: 99%